A high-resolution air pollutants emission inventory in 2013 for the Beijing-Tianjin-Hebei region, China. (December 2017) - Qi, Ji; Zheng, Bo; Li, Meng; Yu, Fang; Chen, Chuchu; Liu, Fei; Zhou, Xiafei; Yuan, Jing; Zhang, Qiang; He, Kebin
Abstract: We developed a high-resolution Beijing-Tianjin-Hebei (BTH) regional air pollutants emission inventory for the year 2013. The inventory was established using a bottom-up approach based on facility-level activity data obtained from multiple data sources. The estimates from the BTH 2013 emission inventory show that the total emissions of SO2, NOX, PM2.5, PM10, CO, NMVOC, NH3, BC, and OC were 2, 305, 2, 686, 1, 090, 1, 494, 20, 567, 2, 207, 623, 160, and 254 Gg, respectively. The industry sector is the largest emissions source for SO2, NOX, PM2.5, PM10, CO, and NMVOC in the BTH region, contributing 72.6%, 43.7%, 59.6%, 64.7%, 60.3%, and 70.4% of the total emissions, respectively. Power plants contributed 11.8% and 23.3% of the total SO2 and NOX emissions, respectively. The transportation sector contributed 28.9% of the total NOX emissions. Emissions from the residential sector accounted for 31.3%, 21.5%, 46.6% and 71.7% of the total PM2.5, NMVOC, BC and OC emissions, respectively. In addition, more than 90% of the total NH3 emissions originate from the agriculture sector, with 44.2% from fertilizer use and 47.7% from livestock. The spatial distribution results illustrate that air pollutant emissions are mainly distributed over the eastern and southern BTH regions. Beijing, Tianjin, Shijiazhuang, Tangshan and Handan are the major contributors of air pollutants. The major NMVOC species in the BTH region are ethylene, acetylene, ethane and toluene. Ethylene is the biggest contributor in Tianjin and Hebei. The largest contributor in Beijing is toluene. There is relatively low uncertainty in SO2 and NOX emission estimates, medium uncertainty in PM2.5, PM10 and CO emission estimates, and high uncertainties in VOC, NH3, BC and OC emission estimates. The proposed policy recommendations, based on the BTH 2013 emission inventory, would be helpful to develop strategies for air pollution control. Highlights: An updated high-resolution emission inventory of 2013 for the BTH region is established. Facility-based emissions are calculated for power and key industries sources. The spatial distribution of emission is investigated. The emission inventory is evaluated by uncertainty analysis.